2019
DOI: 10.15414/agrobiodiversity.2019.2585-8246.265-272
|View full text |Cite
|
Sign up to set email alerts
|

The Contents of Catechins And Anthocyanins in the Above-Ground Organs of Plants of Prunus Spinosa L.

Abstract: Carrying out phenological and biochemical studies, the prospect of using the studied varieties of a thorn in breeding programs for obtaining new adaptive, large-fruited varieties and cultivars have been established. The data on the content of catechins and anthocyanins in the bark, leaves, flowers, and fruits of cultivated plants and wild varieties of Prunus spinosa L. are presented. As a result of the study, it was found that the wild variety of Prunus spinosa has a significantly higher content of anthocyanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In another study, it had values of 0.23 [58]. One possible explanation for the discrepancy in this ratio is that P. spinosa L. is a perennial plant that develops in regions with temperate climates like Ukraine [45], Romania, and Portugal, rather than in regions with a continental climate like central Anatolia. Scientific literature indicates that temperature affects the various stages of growth and development in P. spinosa L. [60] species.…”
Section: Nutritional Values Of the Blackthorne Fruitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, it had values of 0.23 [58]. One possible explanation for the discrepancy in this ratio is that P. spinosa L. is a perennial plant that develops in regions with temperate climates like Ukraine [45], Romania, and Portugal, rather than in regions with a continental climate like central Anatolia. Scientific literature indicates that temperature affects the various stages of growth and development in P. spinosa L. [60] species.…”
Section: Nutritional Values Of the Blackthorne Fruitsmentioning
confidence: 99%
“…The focus of Volodymyr and Iryna's 2019 research was on examining the bioactive substances present in various P. spinosa L. plant anatomical parts [45]. Their findings revealed that the anthocyanin content in the bark ranged from 50 to 163 mg/100 g dry matter (dm).…”
Section: The Polyphenol Composition In Various Parts Of the P Spinosa...mentioning
confidence: 99%
“…(Bolvanský and Užík, 2012;Paprstein et al, 2013;Benediková et al, 2016). It is necessary to identify and evaluate genotypes based on the morphometrical and biochemical traits in various conditions, as evidenced by the many authors (Ivanišová et al, 2017;Vinogradova et al, 2017;Grygorieva et al, 2017aGrygorieva et al, ,b, 2018aFatrcová Šramková et al, 2019;Levon and Golubkova, 2019;Vergun et al, 2020).…”
Section: Introducionmentioning
confidence: 99%